Analisis Kemampuan Keuangan Pemerintah Daerah: Studi Perbandingan Kabupaten/Kota di Provinsi Riau dan Kepulauan Riau - Deddy Candra; Vince Ratnawati; Yesi Mutia (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
This study aimed to determine whether there was statistically difference of local financial capability between Riau Province and Riau Islands Province, as well as what factors affected the receipt of the local revenue (PAD). The method of this research was sequential explanatory model, the research was conducted sequentially, the first stage used the quantitative method and the second stage was continued by the qualitative method. The technique of collecting data used secondary and primary data. Variables of measureing diffences in financial capability by measuring the local financial independence ratio, ratio of fiscal decentralization degree, regional financial dependency ratio, and routine capability index ratio for 2010-2017 using analysis with the Mann Whitney U Test through SPSS 25 for Windows. Furthermore, determining the source of qualitative data with collection techniques using interviews, observation, and documentation. The result showed that there were significant differences in local financial capacity between regencies/cities in Riau Province and Riau Islands Province seen from the Regional Financial Independence ratio, Fiscal Decentralization Degree ratio, Regional Financial Dependency ratio, and Routine Capability Index ratio, in this study the revenue of PAD in the regions was dominated by revenue from the tax sector and if extensification, PAD leakage control, and tax administration improvement were well conducted then it would affect the increase in PAD.